2016
DOI: 10.1111/his.13065
|View full text |Cite
|
Sign up to set email alerts
|

Expression of activated Notch1 and Hey1 in papillary thyroid carcinoma

Abstract: Thus, we found that activation of Notch signalling was correlated significantly with clinicopathological parameters. Therefore, Notch signalling could be a useful prognostic marker in patients with PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
(27 reference statements)
1
11
0
2
Order By: Relevance
“…It has been confirmed in some literature that Notch1 expression is increased in PTC and can promote downstream Jagged1 expression by activating the Notch signaling pathway, affecting the apoptosis, proliferation and invasion of PTC cells (29). In the present study, the Notch signaling pathway inhibitor DAPT was used to treat thyroid carcinoma cells TPC-1.…”
Section: Discussionsupporting
confidence: 65%
“…It has been confirmed in some literature that Notch1 expression is increased in PTC and can promote downstream Jagged1 expression by activating the Notch signaling pathway, affecting the apoptosis, proliferation and invasion of PTC cells (29). In the present study, the Notch signaling pathway inhibitor DAPT was used to treat thyroid carcinoma cells TPC-1.…”
Section: Discussionsupporting
confidence: 65%
“…Jung et al examined the relationship between clinicopathological factors and HEY1 expression in 109 cases of papillary thyroid carcinoma. HEY1 immunoreactivity was positively correlated with lymph node metastasis, recurrence and metastasis [34]. However, Ménard M et al showed that HEY1 inhibited tumor progression by regulating tropomyosin receptor kinase C (TrkC) activity in neuroblastoma [35].…”
Section: Discussionmentioning
confidence: 99%
“…Although differentiated PTC carries a favorable prognosis, it causes a postoperative recurrence rate as high as 30% during long-term follow-up [ 3 ]. A few biomarkers have been identified for the diagnosis of PTC, including EHD2 [ 4 ], Notch signaling [ 5 ], HER-2/neu [ 6 ], and CXCL12 [ 7 ], without clear evidence of their efficacy for clinical use. Therefore, the identification and validation of reliable biomarkers for diagnostic and prognostic prediction of PTC is urgently needed in clinical work.…”
Section: Introductionmentioning
confidence: 99%